2019
DOI: 10.20885/jaai.vol23.iss2.art5
|View full text |Cite
|
Sign up to set email alerts
|

Does the characteristics of regional government and complexity affect on the disclosure regional financial statements?

Abstract: This study aims to analyze the factors that influence the level disclosure of Regional Government Financial Statements. The sample of this study were 101 local government financial statements at Indonesia in 2016-2018. This study uses multiple regression analysis. These results provide that regional wealth, government size, and the number of regional apparatus working units had a significant positive effects on the level of disclosure of Regional Government Financial Statements (RGFS). Whereas the level of dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 8 publications
2
17
0
3
Order By: Relevance
“…Therefore, it can be concluded that there was no significant effect of the number of SKPD on the level of disclosure of the provincial government financial statements in Indonesia. The results of this study are in line with a research conducted by [24] who also mentioned that the number of regional working units does not influence the level of disclosure of regional government financial statements. This is likely because some of the financial management and administration in the SKPDs are still not fully in accordance with the applicable regulations.…”
Section: Multiple Regression Analysissupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, it can be concluded that there was no significant effect of the number of SKPD on the level of disclosure of the provincial government financial statements in Indonesia. The results of this study are in line with a research conducted by [24] who also mentioned that the number of regional working units does not influence the level of disclosure of regional government financial statements. This is likely because some of the financial management and administration in the SKPDs are still not fully in accordance with the applicable regulations.…”
Section: Multiple Regression Analysissupporting
confidence: 90%
“…A study conducted by [3] found that regional wealth has a positive effect on the level of disclosure in provincial government financial statements. The same opinion was mentioned in a research conducted by [24] who also found that regional wealth has a positive and significant effect on the level of disclosure in regional government financial statements. Based on these explanations, the second hypothesis of this study is: H₂: Regional wealth has a positive effect on the level of disclosure in provincial government financial statements.…”
Section: Effect Of Regional Wealth On Level Of Disclosure In Provincial Government Financial Statementssupporting
confidence: 65%
See 3 more Smart Citations